1998
DOI: 10.1093/jac/41.suppl_2.29
|View full text |Cite
|
Sign up to set email alerts
|

Synergic interactions of macrolides and proton-pump inhibitors against Helicobacter pylori: a comparative in-vitro study

Abstract: Thirty-eight clinical strains of Helicobacter pylori were isolated from patients with chronic gastritis and gastroduodenal ulceration, and their susceptibility to macrolide antibiotics (roxithromycin, flurithromycin, azithromycin, erythromycin) in combination with proton-pump inhibitors (lansoprazole and omeprazole) and bismuth subcitrate was assayed. Chequerboard titration was used to analyse the results of antimicrobial interactions and showed that the activity of macrolides was enhanced by combining them wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…Previous studies have shown a synergistic effect of macrolides and PPIs, as indicated by the increased success rate of eradication therapy for Helicobacter pylori in patients receiving macrolides and PPIs versus macrolides alone, and this effect does not appear to be pH-dependent in vitro. The macrolide clarithromycin also inhibits the metabolism of the PPI omeprazole 33,34 . Moreover, we also observed an increase in microbial functions characteristic of the oral bacteria, such as carbohydrate degradation pathways, and an increase in pathways involved in L-arginine biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a synergistic effect of macrolides and PPIs, as indicated by the increased success rate of eradication therapy for Helicobacter pylori in patients receiving macrolides and PPIs versus macrolides alone, and this effect does not appear to be pH-dependent in vitro. The macrolide clarithromycin also inhibits the metabolism of the PPI omeprazole 33,34 . Moreover, we also observed an increase in microbial functions characteristic of the oral bacteria, such as carbohydrate degradation pathways, and an increase in pathways involved in L-arginine biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…сравнивалась активность эритромицина и ази тромицина в отношении H. pylori. МПК 50 в данном иссле довании составляла 0,5 мг/л для обоих препаратов [33].…”
Section: Discussionunclassified
“…The choice of tinidazol was governed by a slightly longer of 12–13 h when compared with 8 h for metronidazol and previous reports of a good effect in other studies 22, 23 . The pharmacological data of a long for both antibiotics and studies in vitro indicating that lansoprazole may act synergetic on azitromycin 24 motivated our choice of a one‐dose per day 6 days PPI‐based triple therapy that in theory would be comparable with a twice daily 7 days therapy.…”
Section: Discussionmentioning
confidence: 99%